Basic analysis of non-European Union immigrants’ hospitalizations and ambulatory care in the province of Ferrara, Northern Italy: the first step to an improved approach to immigrants’ healthcare (Italian Journal of Public Health, 2008)
Background: Immigration towards Ferrara is a recent occurrence. We evaluated the immigrants’ health requests. Methods: This report is based on data collected by Local Health Authority.Results: The analysis of ambulatory cares and hospitalizations are comparable. It emerges the age class 31- 65 is the most represented. Females’ requests are more than males’ one, due to pregnancy and gynaecological health requests. The capital hospital sustained the heaviest workload. We found differences respect European Union population regarding length of stay. The predominant kind of access are through emergency room and self-access.Conclusions: This complex pattern of health care requests requires dedicated approaches.
Keywords: Emigration; immigration; public health; inpatients; outpatients; ambulatory care